Improved subjective symptoms of conjunctivochalasis using bipolar diathermy method for conjunctival shrinkage - Kashima T (Dove Medical Press, 2011)
Tomoyuki Kashima1,2, Hideo Akiyama1, Fumihide Miura2, Shoji Kishi11Department of Ophthalmology, Gunma University School of Medicine, Gunma, Japan; 2Department of Ophthalmology, Saku Central Hospital, Nagano, JapanPurpose: To evaluate the improvement in subjective symptoms of conjunctivochalasis after bipolar coagulation.Methods: Forty-three eyes of 26 patients (average age, 75.7 ± 8.4 years) were included in this study. The inferior conjunctivas were cauterized between April 2009 and June 2010. Surgery involved pinching the excess conjunctiva and performing bipolar cauterization after subconjunctival injection of a local anesthetic agent. Patients were asked to describe the postoperative foreign-body sensation and change in subjective symptoms 1 month postoperatively, with the preoperative symptom score defined as 10.Results: Twenty-two patients (84.6%) reported symptom relief immediately after the procedure, though all patients had a mild gritty sensation for 1–2 weeks postoperatively. The mean postoperative symptom score obtained from the questionnaire was 3.27 ± 3.31, which was significantly lower than the preoperative score (P < 0.0001). No patients had experienced recurrent symptoms at the end of the follow-up period.Conclusion: Thermal cauterization can achieve conjunctival shrinkage and adherence to the subconjunctival tissues. Operation time is only a few minutes, postoperative pain is not severe, and the procedure can be performed in an outpatient clinic, all of which represent benefits to the patients.Keywords: coagulation, cauterization, conjunctival injection